Thermal degradation behavior of methyl methacrylate derived copolymer - Kaya, E.; Kurt A.; Er M. (My University, 2012)
A novel copolymer of 2-hydroxy-3-menthyloxy-1-(4-methoxyphenyl)-3-oxopropyl methacrylate (HMOPMA) and methyl methacrylate (MMA), [poly(HMOPMA-co-MMA)], was synthesized by free radical polymerization. The percentages of HMOPMA and MMA units obtained in the copolymer composition were 19% and 81%, respectively. The solubility parameter of poly(HMOPMA-co-MMA) was found to be 10.3 cal 1/2 cm-3/2 by turbidimetric titration method. Thermal degradation mechanism and activation energies for initial decomposition process under non-isothermal conditions were determined by integral approximation methods from the thermogravimetric study. The decomposition activation energies of poly(HMOPMA-co-MMA) using Kissinger and Flyn-Wall-Ozawa methods were calculated as 119.99 kJ/mol and 125.34 kJ/mol, respectively. The study of kinetic equations showed that the reaction mechanism of decomposition process in the conversion range studied progressed with D1 mechanism, one-dimensional diffusion of deceleration type of solid state mechanism. Copyright © 2012 American Scientific Publishers.
PubMed ID: 23421237
Keywords: Copolymerization; Decomposition activation energy; Solubility parameter; Thermogravimetric analysis